Magnesium alloy material, preparation method thereof and magnesium alloy shell
By retaining dendrite and secondary crystallization structure in the magnesium alloy material and using a semi-solid injection molding method with 4-stage segment heating, the problems of corrosion resistance and dense layer thickness of magnesium alloy material are solved, and workpiece preparation with high density and thick dense layer is achieved.
Patent Information
- Application Number
- CN202411998147.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The corrosion resistance of magnesium alloy materials is weak. Although the corrosion resistance is improved after semi-solid injection molding, there are still problems such as limited thickness of the dense layer and loose holes easily occur during processing.
By retaining the dendrite and secondary crystallized structures in the magnesium alloy material, a magnesium alloy workpiece with high density and thick dense layers was prepared by using a 4-stage segment heating semi-solid injection molding method.
The high density and thick dense layer of magnesium alloy material are achieved, which reduces processing temperature and time, avoids oxidation and blackening and curling problems, and improves the corrosion resistance and processing effect of the workpiece.
Smart Images

Figure BDA0005226700680000171 
Figure BDA0005226700680000191 
Figure HDA0005226700810000011
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to a magnesium alloy material and a preparation method thereof, and a magnesium alloy shell. Background Art
[0002] Magnesium alloys are increasingly being used as the preferred weight-reducing material for 3C products. Among them, the near-net-shape semi-solid injection molding process stands out from the traditional cold-chamber and hot-chamber die-casting processes due to its high density and high-quality appearance of the injected workpieces. It is favored and widely used in the 3C, automotive and other industries. Summary of the invention
[0003] In view of this, the technical problem to be solved by the present application is to provide a magnesium alloy material and a preparation method thereof, and a magnesium alloy shell.
[0004] The present application provides a magnesium alloy material having a dendritic structure and a secondary crystal structure.
[0005] The present application provides a method for preparing a magnesium alloy material, comprising the following steps:
[0006] Smelting;
[0007] Casting to form a dendrite structure in magnesium alloy materials;
[0008] The magnesium alloy material is obtained by heating until the end of the dendrite structure is melted and secondary crystallization occurs, and then cooling is performed to retain the secondary crystal structure.
[0009] The present application provides a method for semi-solid injection molding, comprising:
[0010] Semi-solid injection molding is performed using a magnesium alloy material as a raw material, wherein the magnesium alloy material has a dendritic structure and a secondary crystal structure;
[0011] The semi-solid injection molding is a 4-stage segmented heating method, wherein the heating temperature of the first stage is 510-520°C, the heating temperature of the second stage is 530-550°C, the heating temperature of the third stage is 560-570°C, and the heating temperature of the fourth stage is 580-600°C.
[0012] The present application provides a magnesium alloy shell, which is obtained by semi-solid injection molding using a magnesium alloy material as a raw material, wherein the magnesium alloy material has a dendritic structure and a secondary crystal structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The metallographic structure diagram of the magnesium alloy material prepared in Example 1 of the present application;
[0014] Figure 2This is a cross-sectional view of a product obtained by semi-solid injection molding of the magnesium alloy material prepared in Example 1 of the present application;
[0015] Figure 3 This is a cross-sectional view of a product obtained by semi-solid injection molding of the magnesium alloy material prepared in Comparative Example 5;
[0016] Figure 4 This is the appearance picture of the highlighted product processed from the magnesium alloy material obtained in Example 4 of the present application. DETAILED DESCRIPTION
[0017] It should be noted that, in the absence of conflict, the embodiments and technical features in the embodiments of the present application can be combined with each other, and the detailed description in the specific implementation method should be understood as an explanation of the purpose of the present application and should not be regarded as an improper limitation on the present application.
[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the specific technical solution of the present application will be further described in detail below in conjunction with the drawings in the embodiments of the present application. The following embodiments are used to illustrate the present application, but are not used to limit the scope of the present application.
[0019] In the embodiments of the present application, the terms "first" and "second" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present application, unless otherwise specified, "multiple" means two or more.
[0020] In addition, in the embodiments of the present application, directional terms such as "up", "down", "left" and "right" are defined relative to the orientation of the components in the drawings. It should be understood that these directional terms are relative concepts. They are used for relative description and clarification, and they may change accordingly according to the changes in the orientation of the components in the drawings.
[0021] In the embodiments of the present application, unless otherwise clearly specified and limited, the term "connection" should be understood in a broad sense. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection or an indirect connection through an intermediate medium.
[0022] In the embodiments of the present application, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element.
[0023] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.
[0024] The inventor of this application found that due to the weak corrosion resistance of magnesium alloy, although the corrosion resistance of the molded parts is improved compared with conventional die castings by semi-solid injection molding, the improvement effect is limited. At the same time, the outer surface of the die casting shrinks extremely cold under high filling pressure. Although the dense layer formed has fewer pores, the thickness of the dense layer is limited. During the processing, the outer surface needs to be milled, which easily causes the loose holes on the lower surface to be exposed. In the related technology, chemical conversion or micro-arc oxidation with better corrosion resistance is used to re-treat the magnesium alloy substrate, and a thick coating is used on its surface to ensure that the product meets the requirements of transportation, storage, and daily use. Although the above treatment allows the material to meet the product requirements, the heavy anti-corrosion treatment strictly protects the material, and the metallic feel of the material itself cannot be reflected, which reduces the quality and application effect of the material.
[0025] In view of the above technical problems, the present application provides a magnesium alloy material having a dendritic structure and a secondary crystal structure.
[0026] The dendritic structure is a microstructure formed during the cooling process of casting after the magnesium alloy raw material is smelted.
[0027] The microstructure is a material structure and morphology formed within the metal material within the micrometer scale. The secondary crystal structure is a secondary crystal structure formed after the end of the dendrite structure is melted.
[0028] The secondary crystal structure refers to the microstructure formed when the magnesium alloy material undergoes structural transformation under heating after the magnesium alloy material forms a dendritic structure through primary crystallization.
[0029] The secondary crystal structure may have a spherical or quasi-spherical grain shape.
[0030] The spherical shape may also be called a near-spherical shape or a nearly spherical shape, and its shape is characterized by uniform diffusion outward from a central point, with edge lines being arc-shaped, and the curvatures of these arcs are roughly the same.
[0031] The present application simultaneously retains the dendritic structure and the secondary crystal structure inside the magnesium alloy material, thereby making it easier to be processed into a semi-solid slurry, reducing the processing temperature, and / or shortening the processing time.
[0032] In some embodiments of the present application, the components of the magnesium alloy material may include: Mg and rare earth elements;
[0033] The rare earth element and Mg form a solid solution, providing a crystal nucleus for a secondary crystal structure.
[0034] In the process of melting the end of the dendritic structure, the solid solution formed by the rare earth element and Mg can act as a crystal nucleus to promote the formation of secondary crystalline structure, thereby increasing the formation speed of the secondary crystalline structure. The dendritic structure and the secondary crystalline structure can be retained at the same time by cooling.
[0035] The addition of rare earth elements can refine the grains of the material and improve the mechanical strength of the material by forming a solid solution with magnesium.
[0036] The rare earth element may include one or more of Ce, La, and Y.
[0037] The mass content of Ce in the magnesium alloy material is 3.0% to 4.0%, and can be 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0038] The mass content of La in the magnesium alloy material is 0.3% to 0.5%, and may be 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0039] The mass content of Y in the magnesium alloy material is 0.2% to 0.25%, and may be 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0040] Rare earth elements can be well dissolved in Mg within the above content range.
[0041] The components of the magnesium alloy material may also include Al;
[0042] The Al and the rare earth element form an intermetallic compound to provide a crystal nucleus for a secondary crystal structure.
[0043] In the process of melting the end of the dendritic structure, the intermetallic compound formed by the Al and the rare earth element can act as a crystal nucleus to promote the formation of secondary crystallization structure, further increasing the formation speed of the secondary crystallization structure, so that the dendritic structure and the secondary crystallization structure can be easily retained in the crystal phase of the magnesium alloy material at the same time.
[0044] The intermetallic compound also has the function of improving the corrosion resistance of the material, can improve the corrosion resistance of the magnesium alloy material, make the prepared magnesium alloy material have good density, and can be used to prepare high-brightness and high-gloss workpieces.
[0045] The mass content of Al in the magnesium alloy material is 6.5% to 7.5%, and can be 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7.0%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0046] The Al element can form intermetallic compounds with rare earth elements well within the above content range. If the Al content is too high, it is easy to form large particles of intermetallic compounds with rare earth elements, forming larger intermetallic compounds, and the high density is easy to cause sedimentation; if the Al content is too low, the amount of intermetallic compounds formed is too low, and the spherical structure formed by secondary crystallization is too small.
[0047] The solid solution of the above rare earth elements in magnesium and the intermetallic compounds formed can all serve as secondary crystallization nuclei. As the number of nuclei increases, the crystal nucleation rate is higher than the growth rate, and the number of spherical secondary crystals formed is large and small, which is beneficial to the subsequent semi-solid forming and processing of products. Usually, due to the combined effect of the two, the size of the spherical secondary crystals formed is generally 3 to 5 μm, and the spherical structure accounts for about 60% to 80% of the total volume.
[0048] The components of the magnesium alloy material may include Mg, Al, Ce, La, Y and Mn.
[0049] The contents of Al, Ce, La and Y are as mentioned above.
[0050] The mass content of Mn in the magnesium alloy material is 0.05% to 0.15%, and can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0051] The addition of Mn can effectively remove harmful impurity element iron in the alloy. At the same time, the addition of Mn element is helpful to improve the corrosion resistance of the material.
[0052] The Mn element within the above content range can reduce the content of the iron element to below 0.005%.
[0053] In some embodiments of the present application, the magnesium alloy material also includes inevitable impurities, which are inevitably introduced into the raw materials.
[0054] The unavoidable impurities may be one or more of Fe, Ni, Cu, and Si.
[0055] The mass content of Fe may be lower than 0.005%.
[0056] The mass content of Ni may be lower than 0.01%.
[0057] The mass content of Cu may be lower than 0.01%.
[0058] The mass content of Si may be lower than 0.01%.
[0059] The mass content of the above elements is calculated based on the magnesium alloy material as a whole being 100%, with Mg making up 100%.
[0060] The magnesium alloy material may be an ingot or a granular material, but is not limited thereto.
[0061] In some embodiments of the present application, the size of the magnesium alloy particle material may be 2.0-2.5 mm in length, 5.5-6.0 mm in width, and 1.0-1.5 mm in thickness.
[0062] The above-mentioned magnesium alloy material provided in the present application can realize the transformation from solid to semi-solid slurry at 570-600°C within 3-5s, avoiding the oxidation and blackening problem caused by long-term high-temperature heating, and avoiding the air entrainment problem caused by shearing and flow.
[0063] On the other hand, the present application provides a method for preparing the above-mentioned magnesium alloy material, comprising the following steps:
[0064] Smelting;
[0065] Casting to form a dendrite structure in magnesium alloy materials;
[0066] The magnesium alloy material is obtained by heating until the end of the dendrite structure is melted and secondary crystallization occurs, and then cooling is performed to retain the secondary crystal structure.
[0067] The present application does not limit the raw materials for the smelting. Magnesium and a rare earth element alloy may be mixed for smelting, or magnesium, aluminum and a rare earth element alloy may be mixed for smelting, or magnesium, aluminum, a rare earth element alloy and MnCl2 may be mixed for smelting.
[0068] In some embodiments of the present application, a magnesium ingot and a rare earth element alloy may be mixed for alloying smelting.
[0069] In some embodiments of the present application, an aluminum ingot may be mixed with a magnesium ingot and a rare earth element alloy for alloying and smelting.
[0070] In some embodiments of the present application, an aluminum ingot may be mixed with a magnesium ingot, a rare earth element alloy, and MnCl2 for alloying and smelting.
[0071] In some embodiments of the present application, the rare earth element alloy may be an alloy including one or more of cerium, lanthanum, and iridium.
[0072] The ratio of the aluminum ingot, magnesium ingot, rare earth element alloy and MnCl2 can be adjusted according to the above-mentioned magnesium alloy composition.
[0073] In some embodiments of the present application, the smelting temperature may be 710-750°C.
[0074] In some embodiments of the present application, the molten alloy liquid may be protected by a flame retardant protective gas.
[0075] The flame retardant protective gas is not limited in the present application, and includes but is not limited to helium, argon, sulfur hexafluoride, etc.
[0076] In some embodiments of the present application, further refining may be performed after smelting to remove impurities.
[0077] In some embodiments of the present application, a refining agent or the like may be added during the refining process to remove hydrogen and floating oxide inclusions in the molten liquid, thereby improving the purity of the magnesium alloy.
[0078] In some embodiments of the present application, the refining temperature may be 720-730°C.
[0079] In some embodiments of the present application, the refining time may be 5 to 10 minutes.
[0080] The refining agent can also be added during the smelting process to remove impurities.
[0081] After smelting, the melt can be left to stand for casting.
[0082] In some embodiments of the present application, the casting can be performed under continuous water cooling conditions to achieve rapid casting and allow the material to form a dendritic structure.
[0083] The above-mentioned continuous water cooling refers to cooling under the action of circulating water.
[0084] In some embodiments of the present application, the casting molding may be:
[0085] The molten metal is cooled to 620-630°C and cast under continuous water cooling.
[0086] The present application does not limit the shape of the casting, including but not limited to conventional shapes such as strips and blocks.
[0087] The material obtained by casting is then heated until the end of the dendrite structure is melted and secondary crystallization occurs, and then cooled to retain the secondary crystal structure to obtain a magnesium alloy material.
[0088] Optionally, the heating temperature is 570-595°C, which can be 570°C, 575°C, 580°C, 585°C, 590°C, 595°C, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0089] Optionally, the heating time is 20 to 40 minutes, which can be 20 minutes, 30 minutes, 40 minutes, or a range value with any of the above values as the upper limit or lower limit, but is not limited thereto.
[0090] Optionally, the cast material is first placed in a steel crucible preheated at 150-250°C, and then the crucible is placed in a box-type resistance furnace at 570-595°C, kept warm for 20-40 minutes, and taken out for quenching.
[0091] Optionally, no other operation is performed between the quenching treatment and the above-mentioned heat preservation, and the crucible is quickly quenched after being taken out, so that the secondary crystal structure is well retained in the crystal phase.
[0092] Under the above heating conditions, a large number of large-sized dendritic structures produced during the casting process can be remelted, the ends of the dendritic structures are molten, and fine secondary crystalline structures are gradually formed. After rapid cooling treatment, a large number of fine secondary crystalline structures and solidified dendritic structures are retained.
[0093] During the above heating process, the magnesium-rare earth solid solution and Al-rare earth intermetallic compound dispersed in the crystal phase gradually precipitate at the grain boundary and gradually grow as a crystal nucleus. The end of the dendrite structure in the original structure remelts and grows around the crystal nucleus, finally forming a spherical or quasi-spherical semi-solid secondary crystal structure. The organizational morphology is effectively solidified and retained by cooling to form a magnesium alloy material with a dendrite structure and a secondary crystal structure. In the subsequent semi-solid injection molding process, the above secondary crystal structure is easily melted by heat, so that the magnesium alloy material quickly forms a semi-solid state.
[0094] Optionally, during the above-mentioned heat preservation process, a layer of covering agent is placed on the surface of the material, and the covering agent can serve as an insulating layer to prevent the surface of the magnesium alloy from contacting with air and oxidizing and burning during the heat treatment process, and also plays a protective role during the metal cooling process.
[0095] Optionally, between the casting and the heating, there is also a homogenization heat treatment to make the metal elements diffuse evenly to reduce segregation.
[0096] Optionally, the temperature of the homogenization heat treatment is 400-450°C, and can be 400°C, 410°C, 425°C, 430°C, 440°C, 450°C, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0097] Optionally, the time for the homogenization heat treatment is 6 to 10 hours, which can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0098] Optionally, after the homogenization heat treatment, air cooling is used.
[0099] The present invention does not limit the shape of the magnesium alloy material, which may include but is not limited to block, granular, etc.
[0100] In some embodiments of the present application, after obtaining the magnesium alloy material, the following steps may also be included:
[0101] The magnesium alloy material is granulated to obtain magnesium alloy particles having a secondary crystal structure.
[0102] The magnesium alloy particles can be used as raw materials for semi-solid injection molding to obtain magnesium alloy workpieces.
[0103] The present application provides a method for semi-solid injection molding, comprising:
[0104] Semi-solid injection molding is performed using a magnesium alloy material as a raw material, wherein the magnesium alloy material has a dendritic structure and a secondary crystal structure;
[0105] The semi-solid injection molding is a 4-stage segmented heating method, wherein the heating temperature of the first stage is 510-520°C, the heating temperature of the second stage is 530-550°C, the heating temperature of the third stage is 560-570°C, and the heating temperature of the fourth stage is 580-600°C.
[0106] After the magnesium alloy material prepared in the present application is converted into a semi-solid slurry, the solid content can reach 60% to 70%. Its fluidity is weak and its viscosity is high. When performing semi-solid injection molding, a larger injection pressure can be used. The final magnesium alloy workpiece has a higher density and a thicker dense layer.
[0107] Optionally, the heating time of the first stage is 8 to 12 s, which may be 8 s, 9 s, 10 s, 11 s, 12 s, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0108] Optionally, the heating time of the second stage is 3 to 7 s, which may be 3 s, 4 s, 5 s, 6 s, 7 s, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0109] Optionally, the heating time of the third stage is 1 to 3 seconds, which may be 1 second, 2 seconds, 3 seconds, or a range value with any of the above values as the upper limit or lower limit, but is not limited thereto.
[0110] Optionally, the heating time of the fourth stage is 1 to 3 seconds, which may be 1 second, 2 seconds, 3 seconds, or a range value with any of the above values as the upper limit or lower limit, but is not limited thereto.
[0111] Among them, the first stage of heating plays a role of preheating, heating the pellets from room temperature to partial melting; the second stage of heating plays a role of raising the temperature to fully melt the secondary crystal structure wrapping the crystal nucleus; the third stage of heating plays a role of heat preservation to maintain the above-mentioned molten state; the fourth stage of heating plays a role of raising the temperature to compensate for the heat loss during the flow of the pellets, maintain the optimal solid-liquid ratio and adjust the viscosity of the liquid, and finally complete the injection molding.
[0112] Optionally, the injection pressure of the semi-solid injection molding is 17.5-19.0 MPa, which can be 17.5 MPa, 18 MPa, 18.5 MPa, 19 MPa, or a range value with any of the above values as the upper limit or lower limit, but is not limited thereto.
[0113] Optionally, the semi-solid injection molding is performed under vacuum conditions.
[0114] Optionally, the injection speed of the semi-solid injection molding is 2300-2400 mm / s, which can be 2300 mm / s, 2350 mm / s, 2400 mm / s, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0115] Optionally, the injection time of the semi-solid injection molding is 15 to 20 ms, and may be 15 ms, 16 ms, 17 ms, 18 ms, 19 ms, 20 ms, or a range value with any of the above values as the upper or lower limit, but is not limited thereto.
[0116] The semi-solid injection molding process comprises the following steps:
[0117] Feeding magnesium alloy pellets into the injection molding machine hopper;
[0118] The alloy particles in the hopper are quantitatively fed into the metal sleeve through the screw quantitative feeding device;
[0119] In the metal sleeve device integrating injection, stirring and conveying functions, a spiral conveying rod is used to apply shear force to the metal particles in the metal sleeve, and the temperature is adjusted during the shearing process to make the magnesium alloy particles slightly melted on the surface, forming a solid-liquid mixed state;
[0120] The semi-solid slurry is injected into a mold by an injection molding machine to form a semi-solid injection molded product.
[0121] Optionally, after obtaining the magnesium alloy workpiece, the method may further include performing a surface treatment on the magnesium alloy workpiece.
[0122] The surface treatment is used to improve the surface quality, corrosion resistance, wear resistance of the material, and to give the material surface special properties. The optional processes include but are not limited to high-gloss polishing, wire drawing, cutting, transparent electrophoresis, anodizing, micro-arc oxidation, powder spraying, PVD vacuum plating, sandblasting, nano-coating and other processes, which can be selected according to the requirements of the parts.
[0123] In the related technology, the semi-solid injection molding process of magnesium alloy requires the shearing and extrusion of the screw and the heating of the material tube in combination with the cooling duct to produce semi-solid slurry during the die-casting process of the equipment to achieve semi-solid molding. The magnesium alloy slurry will be oxidized and blackened due to oxidative combustion after severe shearing, heating and long-term high-temperature flow. The severe shearing and flow will also bring a lot of air to the material, affecting the density of the material, and the thickness of the dense layer is limited. In the subsequent processing process, due to the need to mill the outer surface, it is easy to expose the loose holes on the lower surface, affecting the aesthetics of the product.
[0124] The magnesium alloy material provided in the present application can realize the transformation from solid to semi-solid slurry at a lower temperature and in a shorter time. The workpiece after forming has a high density and a thick dense layer, and subsequent high-gloss precision processing can be realized.
[0125] On the other hand, the present application provides a magnesium alloy shell, which is obtained by semi-solid injection molding using a magnesium alloy material as a raw material, and the magnesium alloy material has a dendritic structure and a secondary crystal structure.
[0126] In some embodiments of the present application, the magnesium alloy shell includes a first surface, and the first surface has a metal mirror effect or a brushed effect.
[0127] The material of the first surface may be the magnesium alloy material provided in the present application.
[0128] Optionally, the magnesium alloy shell includes a first surface and a second surface, the first surface intersects with the second surface, and the first surface has a first appearance effect; the second surface has a second appearance effect different from the first appearance effect, and the first appearance effect is a metal mirror effect or a brushed effect.
[0129] Optionally, a third surface is provided at the junction of the first surface and the second surface, the third surface is smaller in size than the first surface and the second surface, and the third surface has a first appearance effect or a second appearance effect.
[0130] Optionally, both the first surface and the second surface are planes.
[0131] The present application also provides an electronic device, comprising the above-mentioned magnesium alloy housing.
[0132] In order to further illustrate the present application, the following is a detailed description in conjunction with embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present application, rather than limiting the claims of the invention.
[0133] All raw materials in this application have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0134] In the following examples, the refining agent used is commercial No. 2 refining agent, the flame retardant protective gas used is sulfur hexafluoride, and the covering agent used is a magnesium alloy covering agent.
[0135] Example 1
[0136] The material ratio is shown in Table 1.
[0137] Preparation method:
[0138] 1) Melting of alloy ingots: The magnesium alloy ingots are melted in a resistance heating crucible furnace. According to the composition of the high brightness and high corrosion resistance magnesium alloy (as shown in Table 1), magnesium ingots, aluminum ingots, rare earth element alloys, MnCl2, and refining agents are added in sequence for alloying and smelting. The melting heating temperature is 730°C, and the molten alloy liquid is protected by flame retardant protective gas.
[0139] 2) Alloy liquid refining and degassing: adjust the alloy liquid temperature to 720℃, add refining agent for refining treatment for 5 minutes;
[0140] 3) Let the melt stand, lower the temperature to 625°C, and rapidly cast the strip-shaped ingot under continuous water cooling. The formation of dendritic structure of magnesium alloy can be observed under a microscope;
[0141] 4) The alloy ingot is sent to a heat treatment furnace in a box-type resistance furnace at a temperature of 425°C, and after solution treatment for 8 hours, it is taken out for air cooling;
[0142] 5) Dry the ingot, put it into a steel crucible preheated at 200°C, evenly sprinkle a layer of covering agent on it, quickly put it into a box-type resistance furnace at 580°C, keep it warm for 30 minutes, quickly take it out for quenching treatment, and obtain a magnesium alloy material.
[0143] The metallographic structure of the prepared magnesium alloy material was characterized by microscope. Figure 1 As shown, Figure 1 is the metallographic structure diagram of the magnesium alloy material prepared in this embodiment. Figure 1 It can be seen that the crystal phase of the magnesium alloy material has both a dendritic structure and a spherical or quasi-spherical secondary crystal structure.
[0144] After semi-solid injection molding, the product is tested on the cross section, and the thickness of the dense layer is 500μm. Figure 2 shown.
[0145] Example 2
[0146] The material ratio is shown in Table 1.
[0147] Preparation method:
[0148] 1) Melting of alloy ingots: The magnesium alloy ingots are melted in a resistance heating crucible furnace. According to the composition of the high brightness and high corrosion resistance magnesium alloy (as shown in Table 1), magnesium ingots, aluminum ingots, rare earth element alloys, MnCl2, and refining agents are added in sequence for alloying and smelting. The melting heating temperature is 730°C, and the molten alloy liquid is protected by flame retardant protective gas.
[0149] 2) Alloy liquid refining and degassing: adjust the alloy liquid temperature to 720℃, add refining agent for refining treatment for 5 minutes;
[0150] 3) Let the melt stand, lower the temperature to 620°C, and rapidly cast strip-shaped ingots under continuous water cooling. The formation of dendritic structure of magnesium alloy can be observed under a microscope;
[0151] 4) The alloy ingot is sent to a heat treatment furnace in a box-type resistance furnace at a temperature of 425°C, and after solution treatment for 8 hours, it is taken out for air cooling;
[0152] 5) Dry the ingot, put it into a steel crucible preheated at 200°C, evenly sprinkle a layer of covering agent on it, quickly put it into a box-type resistance furnace at 590°C, keep it warm for 30 minutes, quickly take it out for quenching treatment, and obtain a magnesium alloy material.
[0153] Microscopic examination revealed that the crystal phase has both dendritic structure and spherical and quasi-spherical secondary crystal structures.
[0154] After semi-solid injection molding, the product was cross-sectioned and the thickness of the dense layer of the magnesium alloy material was 490μm.
[0155] Example 3
[0156] The material ratio is shown in Table 1.
[0157] Preparation method:
[0158] 1) Melting of alloy ingots: The magnesium alloy ingots are melted in a resistance heating crucible furnace. According to the composition of the high brightness and high corrosion resistance magnesium alloy (as shown in Table 1), magnesium ingots, aluminum ingots, rare earth element alloys, MnCl2, and refining agents are added in sequence for alloying and smelting. The melting heating temperature is 735°C, and the molten alloy liquid is protected by flame retardant protective gas.
[0159] 2) Alloy liquid refining and degassing: adjust the alloy liquid temperature to 720℃, add refining agent for refining treatment for 5 minutes;
[0160] 3) Let the melt stand, lower the temperature to 630°C, and rapidly cast strip-shaped ingots under continuous water cooling. The formation of dendritic structure of magnesium alloy can be observed under a microscope;
[0161] 4) The alloy ingot is sent to a heat treatment furnace in a box-type resistance furnace at a temperature of 425°C, and after solution treatment for 8 hours, it is taken out for air cooling;
[0162] 5) Dry the ingot, put it into a steel crucible preheated at 200°C, evenly sprinkle a layer of covering agent on it, quickly put it into a box-type resistance furnace at 590°C, keep it warm for 30 minutes, quickly take it out for quenching treatment, and obtain a magnesium alloy material.
[0163] Microscopic examination revealed that the crystal phase has both dendritic structure and spherical and quasi-spherical secondary crystal structures.
[0164] After semi-solid injection molding, the product was cross-sectioned and the thickness of the dense layer of the magnesium alloy material was 470μm.
[0165] Example 4
[0166] The material ratio is shown in Table 1.
[0167] Preparation method:
[0168] 1) Melting of alloy ingots: The magnesium alloy ingots are melted in a resistance heating crucible furnace. According to the composition of the high brightness and high corrosion resistance magnesium alloy (as shown in Table 1), magnesium ingots, aluminum ingots, rare earth element alloys, MnCl2, and refining agents are added in sequence for alloying and smelting. The melting heating temperature is 745°C, and the molten alloy liquid is protected by flame retardant protective gas.
[0169] 2) Alloy liquid refining and degassing: adjust the alloy liquid temperature to 720℃, add refining agent for refining treatment for 5 minutes;
[0170] 3) Let the melt stand, lower the temperature to 625°C, and rapidly cast the strip-shaped ingot under continuous water cooling. The formation of dendritic structure of magnesium alloy can be observed under a microscope;
[0171] 4) The alloy ingot is sent to a heat treatment furnace in a box-type resistance furnace at a temperature of 425°C, and after solution treatment for 8 hours, it is taken out for air cooling;
[0172] 5) Dry the ingot, put it into a steel crucible preheated at 200°C, evenly sprinkle a layer of covering agent on it, quickly put it into a box-type resistance furnace at 595°C, keep it warm for 30 minutes, quickly take it out for quenching treatment, and obtain a magnesium alloy material.
[0173] Microscopic examination revealed that the crystal phase has both dendritic structure and spherical and quasi-spherical secondary crystal structures.
[0174] After semi-solid injection molding, the product was cross-sectioned and the thickness of the dense layer of the magnesium alloy material was 550μm.
[0175] Embodiments 5 to 7
[0176] The material ratio is shown in Table 1.
[0177] The preparation method is the same as that of Example 1.
[0178] Test results:
[0179] Embodiment 5:
[0180] Microscope examination showed that the crystal phase had both dendritic structure and spherical and quasi-spherical secondary crystal structure, but the secondary crystal structure was very small; after semi-solid injection molding, the product was cross-sectioned and the thickness of the dense layer of the magnesium alloy material was 200μm.
[0181] Embodiment 6:
[0182] Microscope examination showed that the crystal phase only had dendritic structure, and almost no secondary crystal structure was formed. After semi-solid injection molding, the product was cross-sectioned and the thickness of the dense layer of the magnesium alloy material was 100μm.
[0183] Embodiment 7:
[0184] Microscope examination showed that the crystal phase had both dendritic structure and spherical and quasi-spherical secondary crystal structure, but the secondary crystal structure was very small; after semi-solid injection molding, the product was cross-sectioned and the thickness of the dense layer of the magnesium alloy material was 180μm.
[0185] Comparative Example 1
[0186] The material ratio is the same as that in Example 1.
[0187] Preparation method:
[0188] 1) Melting of alloy ingots: The magnesium alloy ingots are melted in a resistance heating crucible furnace. According to the composition of the high-brightness and high-corrosion-resistant magnesium alloy, magnesium ingots, aluminum ingots, rare earth element alloys, MnCl2, and refining agents are added in sequence for alloying and smelting. The melting heating temperature is 735°C, and the molten alloy liquid is protected by flame retardant protective gas.
[0189] 2) Alloy liquid refining and degassing: adjust the alloy liquid temperature to 720℃, add refining agent for refining treatment for 5 minutes;
[0190] 3) Let the melt stand, lower the temperature to 630°C, and rapidly cast strip-shaped ingots under continuous water cooling;
[0191] 4) The alloy ingot is sent to a heat treatment furnace in a box-type resistance furnace at a temperature of 425° C. After solution treatment for 8 hours, the ingot is taken out for air cooling to obtain a magnesium alloy material.
[0192] Test results:
[0193] Microscope examination shows that the tissue formed by the material is still a free solidification tissue, with a large amount of dendritic tissue, and no spherical tissue can be obtained. The semi-solid forming process using this process cannot produce a product with a semi-solid tissue, and the thickness of the dense layer is less than 100μm.
[0194] Comparative Example 2
[0195] The material ratio is the same as that in Example 1.
[0196] Preparation method:
[0197] 1) Melting of alloy ingots: The magnesium alloy ingots are melted in a resistance heating crucible furnace. According to the composition of the high-brightness and high-corrosion-resistant magnesium alloy, magnesium ingots, aluminum ingots, rare earth element alloys, MnCl2, and refining agents are added in sequence for alloying and smelting. The melting heating temperature is 735°C, and the molten alloy liquid is protected by flame retardant protective gas.
[0198] 2) Alloy liquid refining and degassing: adjust the alloy liquid temperature to 720℃, add refining agent for refining treatment for 5 minutes;
[0199] 3) Let the melt stand, lower the temperature to 630°C, and rapidly cast strip-shaped ingots under continuous water cooling;
[0200] 4) The alloy ingot is sent to a heat treatment furnace in a box-type resistance furnace at a temperature of 425°C, and after solution treatment for 8 hours, it is taken out for air cooling;
[0201] 5) Dry the ingot, put it into a steel crucible preheated at 200°C, evenly sprinkle a layer of covering agent on it, quickly put it into a box-type resistance furnace at 620°C, keep it warm for 30 minutes, quickly take it out for quenching treatment, and obtain a magnesium alloy material.
[0202] Test results:
[0203] Microscope inspection shows that due to the high temperature, the dendritic structure basically disappears, and the structure formed by the material contains a small amount of spherical structure. The semi-solid forming process of this process obtains a product with a semi-solid structure, and the thickness of the dense layer is about 85μm, which is not conducive to subsequent processing.
[0204] Comparative Example 3
[0205] The material ratio is the same as that in Example 1.
[0206] Preparation method:
[0207] 1) Melting of alloy ingots: The magnesium alloy ingots are melted in a resistance heating crucible furnace. According to the composition of the high brightness and high corrosion resistance magnesium alloy (as shown in Table 1), magnesium ingots, aluminum ingots, rare earth element alloys, MnCl2, and refining agents are added in sequence for alloying and smelting. The melting heating temperature is 735°C, and the molten alloy liquid is protected by flame retardant protective gas.
[0208] 2) Alloy liquid refining and degassing: adjust the alloy liquid temperature to 720℃, add refining agent for refining treatment for 5 minutes;
[0209] 3) Let the melt stand, lower the temperature to 630°C, and rapidly cast strip-shaped ingots under continuous water cooling;
[0210] 4) The alloy ingot is sent to a heat treatment furnace in a box-type resistance furnace at a temperature of 425°C, and after solution treatment for 8 hours, it is taken out for air cooling;
[0211] 5) Dry the ingot, put it into a steel crucible preheated at 200°C, evenly sprinkle a layer of covering agent on it, quickly put it into a box-type resistance furnace at 565°C, keep it warm for 30 minutes, quickly take it out for quenching treatment, and obtain a magnesium alloy material.
[0212] Test results:
[0213] Microscope examination showed that the material formed a small amount of spherical tissue, and a large amount of dendritic tissue was retained. It could not fill the mold cavity in semi-solid injection molding. The thickness of the dense layer of the product was relatively thin, about 200μm, which was not conducive to subsequent processing.
[0214] Table 1 Content of each component in Examples 1 to 7
[0215]
[0216] Example 8
[0217] The surface oxide layer of the magnesium alloy ingots prepared in Examples 1 to 7 was milled off, and the ingots were placed in a pelletizer for pelletizing to obtain pellets with a size of 2.0 to 2.5 mm in length, 5.5 to 6.0 mm in width, and 1.0 to 1.5 mm in thickness.
[0218] Semi-solid injection molding process parameters are as follows:
[0219] The Japanese JSW650T semi-solid injection molding machine is used. The barrel section heating is a 4-stage segmented heating, combined with a 3-stage temperature heating zone in the nozzle area. Among them, the first section heating temperature of the barrel section is H1: 510-520°C, and the heating time is 10s; the second section heating temperature is H2: 530-550°C, and the heating time is 5s; the third section heating temperature is H3: 560-570°C, and the heating time is 2s; the fourth section heating temperature is H4: 580-600°C, and the heating time is 2s; the nozzle section temperature is set to NH: 600-610°C; NH2: 590-600°C; LNH: 570-580°C.
[0220] The injection mold temperature is set to 170-180°C.
[0221] Injection pressure: 19.0Mpa.
[0222] Injection speed: 2400mm / s.
[0223] Ejection time 15ms.
[0224] The magnesium alloy ingots prepared in Comparative Examples 1 to 3 and the AZ91D magnesium alloy were used as controls (Comparative Example 4).
[0225] Comparative Example 5
[0226] Using AZ91D magnesium alloy as raw material,
[0227] The surface oxide layer is milled off, and the mixture is put into a granulator for granulation to obtain particles with a size of 2.0-2.5 mm in length, 5.5-6.0 mm in width, and 1.0-1.5 mm in thickness.
[0228] Semi-solid injection molding process parameters are as follows:
[0229] The Japanese JSW650T semi-solid injection molding machine is used. The barrel section heating is a 4-stage segmented heating, combined with a 3-stage temperature heating zone in the nozzle area. Among them, the first section heating temperature of the barrel section is H1: 540-550°C, and the heating time is 15s; the second section heating temperature is H2: 600-610°C, and the heating time is 9s; the third section heating temperature is H3: 610-620°C, and the heating time is 5s; the fourth section heating temperature is H4: 615-625°C, and the heating time is 5s; the nozzle section temperature is set as NH: 600-610°C; NH2: 590-600°C; LNH: 570-580°C.
[0230] The injection mold temperature is set to 170-180°C.
[0231] Injection pressure: 16.5Mpa.
[0232] Injection speed: 2400mm / s.
[0233] Ejection time 20ms.
[0234] The test results are shown in Table 2:
[0235] Table 2
[0236]
[0237] It can be seen from the results in Table 2 that the magnesium alloy materials provided in Examples 1 to 4 can completely fill the mold cavity when the workpiece is injection molded, which indicates that under the semi-solid injection molding process parameter conditions of Example 8, a semi-solid state is formed, and the dense layer of the obtained workpiece is thicker, and highlight processing can be performed to obtain a workpiece with a highlight appearance. Figure 4 As shown, Figure 4 This is the appearance picture of the highlighted product processed from the magnesium alloy material obtained in Example 4 of the present application.
[0238] In Example 5, Al element is not added, in Example 6, Al and rare earth elements are not added, and in Example 7, Al and Y elements are not added. Under the same semi-solid injection molding process parameters, the obtained magnesium alloy material can completely fill the mold cavity, but the dense layer of the obtained material becomes thinner. This indicates that after the secondary crystallization structure in the magnesium alloy material is reduced, under the same semi-solid injection molding process parameters, the proportion of liquid phase in the semi-solid state increases due to the reduction of the secondary crystallization spherical structure. Although the filling capacity is improved, the defects such as air entrainment and looseness increase, resulting in a thinning of the dense layer thickness.
[0239] Comparative Example 1 did not perform secondary crystallization treatment, and the obtained magnesium alloy material had no secondary crystallization structure. In Comparative Example 2, the temperature of secondary crystallization was high, and the obtained magnesium alloy material had less secondary crystallization structure. Although the mold cavity was filled in semi-solid injection molding, the obtained product had defects in appearance and a thin dense layer. In Comparative Example 3, the temperature of secondary crystallization was low, and the obtained magnesium alloy material had less secondary crystallization structure. Under this condition, the mold cavity could not be completely filled, and the thickness of the dense layer of the product was also insufficient.
[0240] Comparative Example 4 uses conventional AZ91D particles. Under the semi-solid injection molding process parameter conditions of the present application, since a semi-solid slurry cannot be fully formed in the barrel of the molding machine, the mold cavity cannot be filled and only 75% of the mold cavity volume can be filled. The resulting workpiece has larger defects and a thinner dense layer.
[0241] Comparative Example 5 uses conventional AZ91D particles, and the temperature of semi-solid injection molding is increased and the time is extended to form a semi-solid slurry. However, due to the high temperature, the liquid phase component accounts for a large proportion, the formed product has more defects and the dense layer is thin.
[0242] The above embodiments and comparative examples show that in the present application, the addition of aluminum and rare earth elements has an important influence on the formation of secondary crystallization structure. The solid solution formed by rare earth elements and Mg and the intermetallic compounds formed by rare earth elements and aluminum are conducive to the formation of a large number of spherical secondary crystallization structures. After semi-solid processing into products, the thickness of the dense layer of the formed product increases with the increase of rare earth and aluminum content, which is beneficial to subsequent machining and highlight processing.
[0243] The description of the above embodiments is only used to help understand the method and core idea of the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made to the present application without departing from the principles of the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.
Claims
1. A magnesium alloy material having a dendritic structure and a secondary crystal structure.
2. The magnesium alloy material according to claim 1, characterized in that: The components of the magnesium alloy material include: Mg and rare earth elements; The rare earth element and Mg form a solid solution, providing a crystal nucleus for a secondary crystal structure.
3. The magnesium alloy material according to claim 2, characterized in that: The magnesium alloy material also includes Al as a component; The Al and the rare earth element form an intermetallic compound to provide a crystal nucleus for a secondary crystal structure.
4. The magnesium alloy material according to claim 1, characterized in that: The components of the magnesium alloy material include: Mg, Al, Ce, La, Y and Mn.
5. A method for preparing a magnesium alloy material, comprising the following steps: Smelting; Casting to form a dendrite structure in magnesium alloy materials; The magnesium alloy material is obtained by heating until the end of the dendrite structure is melted and secondary crystallization occurs, and then cooling is performed to retain the secondary crystal structure.
6. The preparation method according to claim 5, characterized in that: The casting molding is as follows: The molten metal is cooled to 620-630°C and cast under continuous water cooling.
7. The preparation method according to claim 5, characterized in that: The heating temperature is 570-595° C.; the heating time is 20-40 minutes.
8. A method of semi-solid injection molding comprising: Semi-solid injection molding is performed using a magnesium alloy material as a raw material, wherein the magnesium alloy material has a dendritic structure and a secondary crystal structure; The semi-solid injection molding is a 4-stage segmented heating method, wherein the heating temperature of the first stage is 510-520°C, the heating temperature of the second stage is 530-550°C, the heating temperature of the third stage is 560-570°C, and the heating temperature of the fourth stage is 580-600°C.
9. The method of semi-solid injection molding according to claim 8, characterized in that: The heating time of the first stage is 8 to 12 seconds; The heating time of the second stage is 3 to 7 seconds; The heating time of the third stage is 1 to 3 seconds; The heating time of the fourth stage is 1 to 3 seconds; The injection pressure of the semi-solid injection molding is 17.5-19.0 MPa.
10. A magnesium alloy shell, obtained by semi-solid injection molding using a magnesium alloy material as a raw material, wherein the magnesium alloy material has a dendritic structure and a secondary crystal structure.